Radars in transportation - Schejbal, Vladimír; Bezoušek, Pavel; Hnilička, Tomáš; Zálabský, Tomáš; Závodný Vadim, / (University of Pardubice, 2018)
The key concept of radar is relatively simple but its practical implementation could be very complicated. An active radar radiates electromagnetic energy and detects the echo returned from reflecting objects (targets). The nature of the echo signal provides information about the target. The distance to the target determines the time of the radiated energy to travel to the target and back. The angular location defines a directive antenna. A radar can derive the target trajectory, and predict future location. With sufficiently high resolution, the radar can distinguish something about a target's size and shape. Usually, the radar is an active device in that it carries its own transmitter and does not depend on ambient radiation, as do most optical and infrared sensors. The radar can detect relatively small targets at near or far distances and can measure their range with precision in all weather. On the other side, the passive surveillance technology provides an unmatched ability to "see without being seen" and provides the very advanced technology. The described properties are very useful for transportation. The students of University of Pardubice and their teachers have cooperated on the development of various kinds of radars produced in the Czech Republic. Several examples such as air traffic control, river and automotive radars, which are used in transportation, are briefly illustrated.
Keywords: radar; transportation; radar principles; radar applications